Simple Clinical Predictors of Successful Fibrinolysis in Combined Assessment of ST-Segment Resolution, Myocardial Infraction Flow Grade, and Myocardial Perfusion Grade: Importance of Admission Blood Glucose and Ischemic Time - Fahmy Rusnanta; Mohammad Saifur Rohman; Indra Prasetya; Ardian Rizal; Novi Kurnianingsih (Universitas Brawijaya, 2021)
Background : Fibrinolytic therapy (FT) is the alternative recommendation in patients with ST-segment elevation myocardial infarction (STEMI) if primary percutaneous coronary intervention (PCI) could not be perfomed timely at initial presentation. Successful revascularization of occluded infarct-related coronary arteries depends on complex mechanisms of hemodynamic, clinical, biochemical, and mechanical parameters. The aim of study was to find outpredictors of patient characteristics to achieve complete reperfusion based on Thrombolysis in Myocardial Infarction(TIMI) 3 flow, Myocardial Blush Grade (MBG) 3, and ST-segment resolution. Method : This retrospective study was held in Saiful Anwar, Malang Hospital during 2017-2021, including total of 142 patients. All patients received FT and coronary angiographic evaluation post-FT. Those were divided into 3 groups, which included R0,1 (0/1 highest measure of reperfusion), R2 (2 highest measures of reperfusion), and R3 (3 highest measures of reperfusion). Results : Ischemic time (OR 0,82 [95%CI -0,39;-0,01]; p=0,04] and admission blood glucose (ABG) (OR 0,99 [95%CI -0,01;0]; p=0,046] were negatively correlated to the complete restoration of reperfusion (R3). This study revealed that ischemic time <5 hours (AUC 0,742 [95%CI 0,645-0,839]; p=0,000) and ABG <140 mg/dL (AUC 0,701 [95%CI 0,612-0,790]; p=0,000) were significant predictor for R≥2. Coronary characteristic was not related to measure of reperfusion (p=0,25). Conclusion : Ischemic time <5 hours and ABG <140 mg/dL are important predictors of successful reperfusion post FT (R≥2). Early assessment of patients who are likely to have low parameter reperfusion (R<2) would help promptly preparing for primary PCI.